ABON BANDENG (CHANOS-EHANOS) UNTUK MENINGKATKAN INTAKE NUTRISI PROTEIN DAN KALSIUM PADA BALITA GIZL BURUK: milk fish; shredded; calcium and protein - Diana Evawati (WAHANA, 2014)
The main goal of this study is to descn'be the best composition in producing good shredded which has nutrient content, especiaUy acceptable protein and calcium. The pwpose and the benefit of this research are: to analyze the increase in the intake of protein and calcium for malnutrition children with Ã‚â€¢milk fish shredded. This study uses basic formula of milk shredded that is high in protein and calcium to improve the nutritional intake ofproteinand calcium of infant malnutrition. This research was conducted through quantitative methodology. The experimental approach is to provide threatment sample and perform laboratory tests to determine levels of protein, calcium and analyze the results of treatment trials through color, taste, texsture and level of preference. The results of this research are the effects of different heating times and the protein content of milk fish with a long shredded about 20 minutes is equal to 12.88% on longetheating25 minutes at 10,74 and at 30 minutes long warm of9,31 %. They are not affected significantly. The protein content in milk shredded with different heating times calcium levels were not significantly different by treatment with some degree of warming. From the test results to determine the effectiveness of the heating treatment performed best, shredded obtained by heating 30 minutes